Portal Pencari Kerja Event Organizer (EOZone) Menggunakan Pendekatan User-Centered Design - Catur Istiqomah; Ahmad Hanafi; Netania Indi Kusumaningtyas (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2021)
The need for personnel in an event is one of the keys to the success of an event held. Event Organizer (EO) is one of the containers that can accommodate workers not fixed in accordance with their field that can increase the success of an event because it is filled with experienced people. EOZone is one of the containers that handle various art events, sports, and other events. The author designed and built an EOZone that aims to accommodate job seekers in finding and obtaining information that requires personnel in an event. The system was developed using a User-Centered Design (UCD) approach that is able to provide information and facilitate the application process from job seekers, especially related to event organizers. This research was created with the intention to find out the initial response of job seekers to the system to be built. In the next development, a feature will be built for the job provider to publish the vacancy if the initial response is good. The system is built using the Python programming language with the Flask Framework with MySQL database. The results of this study state that the process contained in the system has run smoothly as evidenced by the results of black box testing. User tests are conducted by providing questionnaires to prospective users and the results show that users agree EOZone can be used as a medium to help job seekers get information about an event.